The Influence of Electronic Word-of-Mouth in Business Research: Identifying Main Topics and Actors (Journal of Business, Universidad del Pacífico (Lima, Peru), 2025)
AbstractPurpose: The primary goal of this research is to do a systematic review from 2012 to 2022, investigating how the electronic word of mouth is interconnected and their overall research influence.Design/Methodology/Approach: Visualize scientific production employing the Web of Science database and VOS viewer. This study analysed 1449 papers (2012-2022) in Business Economics, identifying influential authors, areas, countries, and journals Co-occurrence of keywords, co-authorship, citation, bibliographic coupling, and co-citation analysis.Findings: This research shed light on the specific aspects of electronic that have gained significant attention and investigation, as well as the global distribution of scholarly contributions, suggesting new areas for further exploration. The main results also reveal that electronic word of mouth is one of the most important topics in Business, Management, and Marketing research. This study bridges knowledge gaps by conducting a thorough thematic evaluation and using systematic analysis to provide a more comprehensive picture of electronic word-of-mouth research across the years. The results provide insight into the development of electronic word of mouth and open up new avenues for study in this area. Originality: Researchers are captivated by the rising significance of Electronic Word-of-Mouth (E-WOM) in the digital age because of its multidisciplinary nature, practical implications for marketing strategies, and dynamic interaction with technology. Thus, a thorough analysis of electronic word-of-mouth research is required, in addition to covering themes from the past, present, and future, studying new aspects of electronic word-of-mouth.
Keywords: Electronic word-of-mouth, (eWOM), science mapping, scientific production analysis